Framing Analysis of Face-To-Face School Reports on CNN Indonesia and Okezone.Com Media: Analisis Framing Pemberitaan Sekolah Tatap Muka pada Media CNN Indonesia dan Okezone.com - Zahroudina, Dinda; Hariyanto, Didik (Indonesian Journal of Innovation Studies, 2023)
This study examines how the framing is carried out by CNN Indonesia and Okezone.com media on the issues discussed by the public regarding the opening of face-to-face schools by the government in the midst of the covid-19 pandemic. This study uses the theory of framing analysis by Robert N. Entman. The purpose of this study was to determine the framing in the news carried out by CNN Indonesia and Okezone.com media on the issue of the implementation of face-to-face schools. This research is descriptive and the method used is qualitative by using Robert N. Entmant's framing analysis. The result of this research is that CNN Indonesia and Okezone frame face-to-face schools as a policy issued by the government because of the ineffectiveness of distance learning. The face-to-face school policy has been regulated and prepared by the government and the two media both pay attention to the policies made by the government.